Analisis Perbandingan Kinerja Keuangan pada PT Mulia Boga Raya TBK dan PT Indofood Sukses Makmur TBK - Yastriana Sajun (Jurnal Syntax Admiration, 2024)
This study aims to analyze whether there are differences in the financial performance of the companies PT Mulia Boga Raya Tbk & PT Indofood Sukses Makmur Tbk during the 2021-2023 period based on liquidity ratios, solvency ratios, profitability ratios, and activity ratios. This type of research is quantitative descriptive with secondary data. The results of this research show that there are differences in the financial performance of PT Mulia Boga Raya Tbk & PT Indofood Sukses Makmur Tbk from 2021-2023. Where the liquidity ratio of PT Mulia Boga Raya Tbk from 2021-2023 is seen from the current ratio, quick ratio, and cash ratio as "Very Good" because it is above the industry average standard, meaning this company has a strong ability to pay off its short-term obligations. Meanwhile, PT Indofood Sukses Makmur Tbk is "Pretty Good" as seen from the current ratio, quick ratio and the cash ratio is "Very Good". The solvency ratio can be seen from the Debt to Asset Ratio and Debt to Equity Ratio of PT Indofood Sukses Makmur Tbk "Very Good" compared to PT Mulia Boga Raya Tbk "Not Good". In the profitability ratio, we look at the Net Profit Margin, return on assets, and Return on Equity of PT Mulia Boga Raya Tbk & PT Indofood Sukses Makmur Tbk "Not Good". In terms of activity ratios seen from Total Assets Turnover and Fixed Assets Turnover, both companies are said to be "Very Good" because they are above the set industry standards.